The Comparison of Cooking Loss, Microbial and Sensory Quality of Patty Burger Using Red Fruit Oil and Virgin Coconut Oil as Fat Replacer - Tharukliling, Selvia; Lawalata, Jacob.J. (Jurnal Ilmu dan Teknologi Hasil Ternak, 2025)
The patties formula generally uses animal fat, the presence of fat can reconstruct the texture of the product, add a distinctive taste and provide a sense of juiciness (mouthfeel) but by this composition patty burgers are included in the unhealthy food category. It is necessary to reformulate the composition of the dough by adding or replacing animal fat ingredients with other ingredients based on fat from vegetable fats.  The aim of this research was to compare the microbial and sensory quality of burger patties using red fruit oil and VCO as substitutes for animal fat in the formulation. The treatments used were patty without the addition of VCO and Red Fruit oil (RFO) as control treatment (P0) and patty with the addition of 10% RFO (P1), patty with addition of 10% VCO (P2), patty with the addition of 20% RFO (P3) and patty with addition of 20% VCO(P4). The variables observed in this research were cooking loss, total plate count (TPC) and sensory quality (color, aroma, texture an juiciness).The result showed the higher percentage of cooking loss is the treatment P2 with 10% level of VCO and the lower percentage of cooking loss is the treatment P3 with 20% level of RFO, and this result in line with other parameters like microbial quality, the safe microbial quality through the Total Plate Count assessment of the raw material patty is the treatment using red fruit oil at the 20% level and VCO at the 10 and 20% level, Meanwhile the sensory quality is for color, aroma, texture and juiciness. The highest score from the panelists was in treatment P3 which used 20% red fruit oil and the lowest score was in treatment P0 (control).